How do cartels operate? - Joseph E. Harrington (Jr.) (The Johns Hopkins University, Department of Economics, 2006)
This paper distills and organizes facts about cartels from about 20 European Commission decisions over 1999-2004. It describes the properties of a collusive outcome, monitoring and punishment methods for enforcing it, the frequency of meetings, the organizational structure of cartels, and what preceded cartel formation.
Keywords: 330